Level of inquiry skills among 6th grade primary school pupils - Čipková, Elena; Fuchs, Michael; Šmida, Dominik (Scientia in educatione, 2023)
The primary aim of science education is to develop the pupils’ scientific literacy that they have a wide range of knowledge, attitudes, competencies, and skills that enable them to use and apply knowledge and procedures associated with scientific inquiry when solving various situations in daily life. An important component of scientific literacy is inquiry skills, through which methods and procedures copying the work of scientists can be applied in solving problems. At the same time, they allow pupils to gain new knowledge and understand natural concepts, based on which they can input more deeply into the way the world works. In the submitted contribution, we present the results of the conducted research aimed at evaluating the level of inquiry skills among sixth-grade pupils of lower secondary education (ISCED 2). The obtained data indicate that the pupils who participated in the research have a relatively low level of inquiry skills, which can significantly affect their ability to search and discover new knowledge in the field of natural sciences and ultimately have a negative impact on their overall level of scientific literacy.